A New Pseudo-Type κ-Fold Symmetric Bi-Univalent Function Class - Sondekola Rudra Swamy; Luminita-Ioana Cotîrlă (Axioms, 2023)
We introduce and study a new pseudo-type <semantics>κ</semantics>-fold symmetric bi-univalent function class that meets certain subordination conditions in this article. For functions in the newly formed class, the initial coefficient bounds are obtained. For members in this class, the Fekete–Szegö issue is also estimated. In addition, we uncover pertinent links to previous results and give a few observations.